1997
DOI: 10.1161/01.str.28.11.2201
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of Ultrasound Assessment of Carotid Plaque Occurrence, Thickness, and Morphology

Abstract: Population screening using B-mode ultrasound provides a valuable means for the detection and morphological evaluation of carotid plaques, whereas measurements of plaque thickness are subject to considerable measurement error.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
109
2
3

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(121 citation statements)
references
References 33 publications
7
109
2
3
Order By: Relevance
“…Some plaques (3%) were defined as unclassifiable because of unsatisfactory imaging quality. 20 The between-and within-sonographer agreement on plaque occurrence was satisfactory, with values of 0.72 (95% CI, 0.60 to 0.84) and 0.76 (95% CI, 0.63 to 0.89), respectively. Agreement on classification of plaque echogenicity was also substantial, with values of 0.73 (95% CI, 0.59 to 0.87) and 0.69 (95% CI, 0.55 to 0.83) between and within sonographers, respectively.…”
Section: Methodsmentioning
confidence: 85%
See 2 more Smart Citations
“…Some plaques (3%) were defined as unclassifiable because of unsatisfactory imaging quality. 20 The between-and within-sonographer agreement on plaque occurrence was satisfactory, with values of 0.72 (95% CI, 0.60 to 0.84) and 0.76 (95% CI, 0.63 to 0.89), respectively. Agreement on classification of plaque echogenicity was also substantial, with values of 0.73 (95% CI, 0.59 to 0.87) and 0.69 (95% CI, 0.55 to 0.83) between and within sonographers, respectively.…”
Section: Methodsmentioning
confidence: 85%
“…19 Carotid atherosclerosis was assessed by use of high-resolution B-mode ultrasonography performed with an ultrasound scanner (Acuson Xp10 128 ART, upgraded) equipped with a linear-array transducer. 20 A plaque was defined as a localized protrusion of the internal part of the vessel wall into the lumen. Maximum plaque thickness was measured online on frozen B-mode images marked with electronic calipers with measurement readout in 10ths of a millimeter.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean intraobserver arithmetic difference (SD) for sonographer 1 was 0.2 (3.1) mm 2 , and the limits of agreement were ±6.1 mm 2 . The corresponding values for sonographer 2 were 0.01 (3.8) and ±7.5 mm 2 [10,15,16].…”
Section: Methodsmentioning
confidence: 86%
“…5,6 Concerning carotid structure, intima-media thickness (IMT), lumen diameter and focal atherosclerosis (plaques) can be visualized and assessed by high-resolution B-mode ultrasound, a noninvasive, valid and reproducible method. 7 Several previous studies have shown positive associations between BMI and IMT. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Relationships between FM and FFM with IMT were assessed in only one recent study with inconclusive results.…”
Section: Introductionmentioning
confidence: 95%